The role of phenolic compounds on olive oil aroma release - Genovese, Alessandro; Yang, Ni; Linforth, Robert; Sacchi, Raffaele; Fisk, Ian (Elsevier, 2018)
In this study, atmospheric pressure chemical ionisation-mass spectrometry (APCI-MS) was successfully applied to understand the effect of phenolic compounds on the release of olive oil aroma compounds. Eight aroma compounds were monitored under in-vivo and in-vitro dynamic conditions in olive oil with and without the addition of virgin olive oil (VOO) biophenols. Three model olive oils (MOOs) were set up with identical volatile compounds concentrations using a refined olive oil (ROO). Phenolics were extracted from VOOs and were added to two MOOs in order to obtain two different concentrations of phenolic compounds (P+ = 354 mg kg−1; P++ = 593 mg kg−1). Another MOO was without VOO biophenols (P−). Phenolic compounds impacted both the intensity and time of aroma release. In the in-vivo study, 1-penten-3-one, trans-2-hexenal and esters had lower release in the presence of higher levels of biophenols after swallowing. In contrast, linalool and 1-hexanol had a greater release. The more hydrophobic compounds had a longer persistence in the breath than the hydrophilic compounds. VOO phenolics-proline-rich proteins complexes could explain the binding of aroma compounds and consequently their decrease during analysis and during organoleptic assessment of olive oil.